Amebic Acute Appendicitis: Systematic Review of 174 Cases - Otan, E; Akbulut, S; Kayaalp, C (2013)
This study aimed to determine the clinical and demographic features of acute amebic appendicitis by reviewing the reported cases. The PubMed and MEDLINE databases were searched to identify articles related to amebic appendicitis using key words. The search included all articles published between 1935 and 2012 without restricting language, journal, or country. A total of 174 cases of amebic appendicitis reported in 42 articles were analyzed. The mean age of the patients was 23.5 years (range 2 months-83 years). The majority of patients were male (74.0 %), and the majority of cases were reported from countries with high/moderate risk for amebiasis (76.5 %). A history of traveling to a high/moderate-risk country was cited in 64.0 % of the overall cases. The interval between travel and onset of clinical symptoms ranged from months to years. History of or coexisting dysenteric diarrhea was present in only 7.0 and 14.0 % of overall cases, respectively. A preoperative diagnosis of amebiasis was cited for only five cases (3.0 %). Complicated appendicitis was present in 30.7 % of cases, some of which required colon resection. Severe postoperative intraabdominal complications (e.g., liver abscess, abdominal sepsis, gastrointestinal fistula, hemorrhage) occurred in 19.4 % of surgery-treated patients. The overall mortality rate was 3.2 %. Appendectomy specimens should be routinely sent for histopathologic examination. In the case of suspected amebic acute appendicitis, extra precautions-early appendectomy, metronidazole for antibiotic prophylaxis, wet-preparation examination, obtaining a timely pathology result, increasing the awareness of uncommon complications of appendectomy-can hasten appropriate therapeutic intervention and improve outcome. C1 [Otan, Emrah; Akbulut, Sami; Kayaalp, Cuneyt] Inonu Univ, Fac Med, Liver Transplantat Inst, Dept Surg, TR-44280 Malatya, Turkey.